2017
DOI: 10.1002/2016ja023066
|View full text |Cite
|
Sign up to set email alerts
|

Assessing ionospheric response during some strong storms in solar cycle 24 using various data sources

Abstract: We present an analysis of a regional ionospheric response during six strong storms (−200 nT ≤Dst≤−100 nT) that occurred in 2012 for the geographic latitudinal coverage of 10°S–40°S within a longitude sector of 10°E–40°E. Although these storms occurred during the same solar activity period and were all coronal mass ejection driven, their impacts and associated features on the ionosphere have been found different due to different contributing factors to their driving mechanisms. With the exception of one case, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…There were four cases where they observed PPEF (i.e., the storm periods, 7–11 March, 22–26 April, 15 July, and 29 September to 3 October 2012). For some storm periods where Habarulema et al () observed P ionospheric storm effects over Southern Hemisphere midlatitude, P ionospheric response were also observed over TDOU and HALY for the time when data were available except in one case (i.e., 6–10 October 2012) where NS ionospheric response was observed over both stations. A significant number of NS ionospheric storm effects were observed over TDOU and HALY stations.…”
Section: Overall Statisticsmentioning
confidence: 88%
See 2 more Smart Citations
“…There were four cases where they observed PPEF (i.e., the storm periods, 7–11 March, 22–26 April, 15 July, and 29 September to 3 October 2012). For some storm periods where Habarulema et al () observed P ionospheric storm effects over Southern Hemisphere midlatitude, P ionospheric response were also observed over TDOU and HALY for the time when data were available except in one case (i.e., 6–10 October 2012) where NS ionospheric response was observed over both stations. A significant number of NS ionospheric storm effects were observed over TDOU and HALY stations.…”
Section: Overall Statisticsmentioning
confidence: 88%
“…Over South Africa, Ngwira et al () reported that the P ionospheric response that occurred on 15 May 2005 was due to TIDs. Habarulema et al () also studied the ionospheric response during six geomagnetic storm periods that occurred in 2012 for the geographical latitudinal coverage of 10°S–40°S within the longitude sector of 10°E–40°E. They observed TIDs during all storm periods.…”
Section: Overall Statisticsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study period spans days of quiet and various magnitudes of disturbed geomagnetic conditions as shown in Figure . The storm period between 7 and 11 March 2012 has been previously studied and different ionospheric aspects reported on both regional and global scales (see, e.g., Habarulema et al, , ). The geomagnetic conditions are classified as weak (−30 nT ≤ D s t <− 50 nT), moderate (−50 nT ≤ D s t <− 100 nT), and strong (−100 nT ≤ D s t <− 200 nT) according to the storm classification by Loewe and Prolss ().…”
Section: Data Analysis and Methodologymentioning
confidence: 99%
“…Models of ionospheric response to geomagnetic storms rely directly on the quality of available data; problems in the data carry straight into these models including biases and larger uncertainty due to erroneous, repeated, and missing observations. To be more specific, the scientific community has used the World Data Center ionospheric database to support innovative research, including studies of both short-and long-term processes (e.g., Araujo-Pradere et al, 2004;Araujo-Pradere et al, 2005;Jarvis et al, 2002;Marin et al, 2001), as well as case studies of individual disturbances, that is, plasma bubble descriptions (Shiokawa et al, 2015), and traveling ionospheric disturbances (Lin et al, 2017), ionospheric response during extreme conditions (Burešová & Laštovička, 2017;Habarulema et al, 2017), and modeling of various purposes (Hernández-Pajares et al, 2017;Liu et al, 2017). Because issues with the quality of the data can substantially affect the outcome of the analyses, feedback from users that are conducting original research based on the data is one of the best ways to detect and possibly correct these issues to decrease their prevalence in the data record.…”
Section: 1029/2018rs006686mentioning
confidence: 99%